Feasibility Analysis Development Dinar Salon At Cipagalo Village - Dinar Imansari; Endang Chumaidiyah; Rosad Ma’ali El Hadi (eProceedings of Engineering, 2016)
Dinar Salon is a beauty salon especially for muslimah at Cipagalo Village that offer variety treatment and beauty product for treatment at home. An increase in the number of women, it can provide opportunities for the Dinar. After do collecting and processing data obtained potential market amounted to 79%, available market amounted to 69%, and target market amounted to 14%. As for the problems faced by Dinsr Salon as the amount of labor that there is only one person and the number of customer who enough fluctuative. In addition, the calculation done on financial aspect. The calculation covers the need of investment fund, the estimate of revenue, operational cost, income statement, cash flow, and balance sheet. Then the calculation that is used to find out the feasibility of investment is Net Present Value (NPV), Pay Back Period (PBP), and Internal Rate of Return (IRR) with the period set for the financial projection is five years. The result of calculation investment is Rp 485.664.545,- retrieved NPV with posirive value Rp 39.862.818,-, IRR by 11,3 % and PBP for 4,87 years. Development Dinar Salon at Cipagalo Village is feasible because the value of IRR obtained is greater than the value of MARR and the NPV is positive. Key words: Feasibility Analysis, NPV, IRR, PBP, Beauty Salon, Village